GISTs-- Gastrointestinal stromal tumors - Castelguidone, Elisabetta de Lutio di; Messina, Antonella (Springer, 2011)
This book aims to provide a complete overview of the diagnosis and treatment of gastrointestinal stromal tumors (GISTs). It has been conceived to be both a detailed guide for clinical practice and an updated reference for all those involved in the evaluation of GISTs imaging. The publication provides comprehensive descriptions of the full range of common imaging and nonimaging techniques used in the diagnosis and followup of GISTs. Techniques reviewed include: Conventional radiography; Endoscopy and endoscopic ultrasound; Conventional, color-Doppler and contrast-enhanced ultrasound.